2019
DOI: 10.1108/mbr-09-2018-0061
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of dynamic managerial capability and international opportunity identification on firm performance

Abstract: Purpose This paper aims to investigate the antecedents and outcomes of international opportunity identification (IOI) in export-manufacturing firms. The fundamental question addressed in this research is: How does dynamic managerial capability (DMC) of entrepreneurs contribute to IOI and success of the firms? Design/methodology/approach The research model was tested through structural equation modeling among the readymade garment manufacturing firms in the least developed country, Bangladesh. A survey was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
1
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(139 citation statements)
references
References 75 publications
5
122
1
11
Order By: Relevance
“…We confirmed that opportunity recognition significantly contributes to SMEs' performance, which is consistent with Hulbert, Gilmore, & Carson () who revealed that entrepreneurs recognize new opportunities for the performance to enhance their profitability. Similarly, Mostafiz et al () also claimed that recognition of new opportunities is very crucial for SMEs' performance due to lack of resources and capabilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We confirmed that opportunity recognition significantly contributes to SMEs' performance, which is consistent with Hulbert, Gilmore, & Carson () who revealed that entrepreneurs recognize new opportunities for the performance to enhance their profitability. Similarly, Mostafiz et al () also claimed that recognition of new opportunities is very crucial for SMEs' performance due to lack of resources and capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Opportunity recognition skills significantly enable entrepreneurs to grow their ventures rapidly (Hulbert, Gilmore & Carson, ). Those managers who have the ability to detect opportunity can enjoy high profitability in the dynamic markets (Mostafiz, Sambasivan, & Goh, ). Therefore,…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding nonfinancial performances, other studies found intangible and immaterial benefits at the individual level and the firm level [2]. At the individual level, the international opportunities process generally enables individuals to expand their cognitive schemas and enhance heuristic decisions to face uncertainty [21,128]. As such, individuals address international market uncertainties with better perceptions of self-efficacy and perceived-desirability and they are equipped with a greater entrepreneurial behavior [87] characterized by high-risk propensity [43], personal proactiveness and commitment [26] that elevates motivation and willingness to face and tolerate uncertainty [21,51].…”
Section: Outcomes Of the International Opportunities Processmentioning
confidence: 99%
“…Mohamad and Sidek (2013) stated that business performance is typically related to the resource-based view (RBV) theory. The RBV of the firm has been frequently utilized in literature over the past 20 years to understand the relationship between a business unit's resources/capabilities and its performance or profitability (Mostafiz, Sambasivan and Goh, 2019b). RBV states that business performance is achieved when the firm has valuable resources and capabilities available as a source of sustainable competitive advantages (Mahoney, 1995).…”
Section: Resource-based View Theory and Potential Resourcesmentioning
confidence: 99%